Witold Lutosławski’s «Venetian Games» for Orchestra: Specifics of Musical Dramaturgy in Aleatoric Composition - Pikush, Yurii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The creative legacy of Witold Lutosławski occupies a central place in the panorama of twentieth-century music, representing a synthesis of strict compositional logic and aleatoric freedom. His orchestral work Venetian Games demonstrates an innovative approach to musical form and dramaturgy through the technique of controlled aleatoricism. The study is relevant because it explores the transformation of compositional thinking in the mid-twentieth century and the evolution of the principles of sound organization that became influential for the development of contemporary orchestral language. Main objective(s) of the study. The main goal of the research is to identify the specific features of the dramaturgical and structural organization of Venetian Games and to determine how the composer combines chance operations with precise structural control to achieve a multilayered artistic result. Methodology (how the study was done). The study employs structural and analytical methods, score analysis, and comparative approaches to reveal the interaction of timbral and rhythmic parameters. The research traces the relationships between instrumental groups and examines the processes of contrast, substitution, and opposition that form the dramatic progression of the composition. Results / findings and conclusions (significance). The analysis shows that Venetian Games exemplifies a deeply reasoned compositional conception based on the alternation of contrasting sound blocks and the development of timbral dramaturgy. Lutosławski’s use of controlled aleatoricism allows him to balance interpretative freedom with structural coherence. The work expands the boundaries of orchestral thinking, offering listeners a complex, multi-level perception of form and motion. Prospects for further research. Future studies may focus on classifying the principles and parameters of ensemble and orchestral dramaturgy, as well as on identifying the composer’s typical strategies of dramaturgical development in the context of aleatoric composition.